Neutrophil/lymphocyte ratio is associated with thromboembolic stroke in patients with non-valvular atrial fibrillation - Ertas, Gokhan; Sonmez, Osman; Turfan, Murat; Kul, Seref; Erdogan, Ercan; Tasal, Abdurrahman; BACAKSIZ, AHMET; BACAKSIZ, AHMET; Vatankulu, Mehmet Akif; Altintas, Ozge; Uyarel, Huseyin; Goktekin, Omer (My University, 2013)
Background: Neutrophil/lymphocyte ratio (NLR) has been associated with poor outcomes in patients with cardiovascular diseases. However, little is known about the role of NLR in patients with thromboembolic stroke due to atrial fibrillation (AF). We aimed to compare the NLR ratios between non-valvular AF patients with or without thromboembolic stroke.